Modulación por Passiflora edulis de triglicéridos y colesterol intracelulares en líneas celulares de cáncer colorrectal SW480 y sus derivadas metastásicas (SW620) (2024)
ABSTRACT: Cancer cells modify lipid metabolism to proliferate, Passiflora edulis (P. edulis) fruit juice (ZuFru) has antitumor activity, but whether a mechanism is through modulation of cell lipids is unknown. To establish if ZuFru modifies cholesterol and triglycerides in SW480 and SW620. ZuFru composition was studied by phytochemical march; antiproliferative activity by sulforhodamine B, cholesterol, and triglycerides by Folch method. Zufru contains anthocyanins, flavonoids, alkaloids, and tannins. Cell lines showed differences in their growth rate (p=0.049). At 39.6 μg/mL of ZuFru, cell viability was decreased: SW480 (45.6%) and SW620 (45.1%). In SW480, cholesterol (44.6%) and triglycerides (46.5%) decreased; In SW620, cholesterol decreased 14.8% and triglycerides increased 7%, with significant differences for both lines. Antiproliferative activity of ZuFru could be associated with the inhibition of intracellular biosynthesis of cholesterol and triglycerides in SW480. Action mechanisms need to be further investigated.